Dissolved Mn(III) in water treatment works: Prevalence and significance. (1st September 2018) - Johnson, Karen L.; McCann, Clare M.; Wilkinson, John-Luke; Jones, Matt; Tebo, Bradley M.; West, Martin; Elgy, Christine; Clarke, Catherine E.; Gowdy, Claire; Hudson-Edwards, Karen A.
Abstract: Dissolved Mn(III) has been identified at all stages throughout a Water Treatment Works (WTW) receiving inflow from a peaty upland catchment in NE England. Ninety percent of the influent total manganese into the WTW is particulate Mn, in the form of Mn oxide (>0.2 μm). Approximately 9% (mean value, n = 22, range of 0–100%) of the dissolved (<0.2 μm) influent Mn is present as dissolved Mn(III). Mn(III) concentrations are highest (mean of 49% of total dissolved Mn; n = 26, range of 17–89%) within the WTW where water comes into contact with the organic-rich sludges which are produced as waste products in the WTW. These Mn(III)-containing wastewaters are recirculated to the head of the works and constitute a large input of Mn(III) into the WTW. This is the first report of Mn(III) being identified in a WTW. The ability of Mn(III) to act as both an oxidant and a reductant is of interest to the water industry. Understanding the formation and removal of Mn(III) within may help reduce Mn oxide deposits in pipe networks. Further understanding how the ratio of Mn(III) to Mn(II) can be used to optimise dissolved Mn removal would save the water industry significant money in reducing discoloration 'events' at the customers' tap. Graphical abstract: Image 1 Highlights: Mn(III) has been identified at all stages for the first time through a water treatment works. Mn(III) can be produced in water treatment works where waters are in contact with organic rich sludges. Knowledge of Mn(II)/(III) speciation within WTW could help the Water Industry to improve Mn removal within WTW.